Efektifitas Pelatihan Strategic Planning Metode Kombinasi untuk Meningkatkan Pemahaman dan Kepuasan Peserta di Dinas Kesehatan Kabupaten Pinrang - Irwandy .; Adelia U. Ady Mangilep; Rini Anggraeni; Farhah Husain Ghanus; Nur Latifah Salman (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
Pinrang Regency is an area with a Regional Medium Term Development Plan (RPJMD) period which will end in 2024 as well as a five-year strategic plan belonging to the Health Service. However, due to simultaneous national regional head elections in 2024, Pinrang Regency has not been able to produce this document due to the fact that a definitive regional head has not yet been elected. To fill the gaps in planning documents while waiting for the Regional Representatives to be elected, the Ministry of Home Affairs instructed them to prepare a strategic plan for the 2025-2026 period. Based on this, an activity with the right method is needed to help the Health Service be able to understand and create strategic plan documents quickly. This community service aims to provide training to the Pinrang District Health Service using a combination method (delivery of material, case studies, and preparation simulations) and assess its effectiveness to increase participants' understanding and satisfaction. The training was held for 2 days and was attended by 30 participants. The results of the Pre-Test quantitative analysis showed that the participants' level of understanding was 10 - 20% understanding and very understanding regarding the material provided, then there was an increase in the Post-Test results, where participants' understanding was 60 - 70% understanding and very understanding. This shows that the activity objectives have been achieved.